The effects of fraud/forgery on a letter of credit: an international perspective - Roslinda Mohamed Fadzil, (Fakulti Undang - Undang, 2000)

(untitled)
With a view to canvassing the principal potential problems in advising upon letters of credit, this article considers the following topics: (i) the documents of a typical credit transaction; (ii) the doctrine of autonomy; (iii) the doctrine of strict compliance and incidence of non-complying documents; (iv) the documents used to check letter of credit terms; (v) the types of fraud; and (vi) the level of burden of proof required in establishing fraud. In particular, this article by looking at case law raises three questions. First, is the doctrine of strict compliance effective when in a majority of transactions the documents tendered are discrepant due to actual fraud and mere fraud? Secondly, what is the appropriate degree of burden of proof used by the courts to justify non-payment for standby credits given the case of perpetrating fraud there under? And lastly, what has caused the demise of the traditional bill of Lading to a more electronic mode of negotiability?